Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Exceeding expectations: economic forecasts and underreaction to macroeconomic announcements - Birz, Gene; Dutta, Sandip (SSRN Electronic Journal, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.fin

Emerging market hedge funds: are they managed like hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2013)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period showthat EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: dept.fin; ⛔ No DOI found

Daytime vs. overnight trading in equity index futures markets - Dutta, Sandip; Sharma, Subhash C (Accounting and Finance Research, 2012)
Keywords: dept.fin; peer-reviewed

Are we overestimating REIT idiosyncratic risk? Analysis of pricing effects and persistence - Abugri, Benjamin A.; Dutta, Sandip (International Review of Economics & Finance, 2014)
This study uses a multifactor REIT-specific model to estimate and compare REIT idiosyncratic volatility vis-A-vis the same from the Fama-French three-factor model. Estimates of conditional idiosyncratic volatility and conditional betas obtained from a multifactor REIT-returns model and a bivariate EGARCH model respectively are found to be positively and significantly related with REIT returns. Consistent with Merton's (1987) predictions, we observe that larger REITs post higher average returns when idiosyncratic risk is introduced in cross-sectional regressions. Persistence of past market-risk does not appear to be short-lived and seems to have a lasting impact on future idiosyncratic volatility. We also observe mild evidence of persistence of past idiosyncratic risk, albeit short-lived, thereby suggesting that past idiosyncratic risk has a short-term impact on future idiosyncratic risk. Published by Elsevier Inc.
Keywords: Conditional betas; Idiosyncratic risk; REITs; dept.fin

Emerging market hedge funds: Do they perform like regular hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2009)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period show that EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: Emerging market hedge funds; Hegde funds; Modified Sharpe Ratio; Portfolio performance measures; Risk-adjusted returns; dept.fin

Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
Keywords: dept.fin; peer-reviewed

Is good news good and bad news bad in the REIT market - Birz, Gene; Devos, Erik; Dutta, Sandip; Tsang, Desmond (Journal of Real Estate Portfolio Management, 2021)
Keywords: dept.fin; peer-reviewed

Ex-ante performance of REIT portfolios - Birz, Gene; Devos, Erik; Dutta, Sandip; Nguyen, Khoa; Tsang, Desmond (Review of Quantitative Finance and Accounting, 2022)
The Real Estate Investment Trust (REIT) market has become an increasingly important vehicle for alternative investment for equity investors. While existing research examining the cross-section of REIT returns usually employs standard risk factors in the in-sample models, it can only show the ex-post performance of REIT portfolios. The goal of our paper is to examine the ex-ante performance of REIT portfolios (i.e., the ability of investors to earn abnormal returns in real time). We employ the out-of-sample methodology of Cooper, Gutierrez, and Marcum (2005), and show that ex-ante performance of REIT portfolios is rather weak. For about half of our 19-year sample over the period of 1999 to 2017, the portfolio performances of REITs chosen ex-ante do not beat the performances of the FTSE-NAREIT or the CRSP Equal-Weighted index. After adjusting for transaction costs, the REIT portfolios significantly further underperform their benchmarks. Overall, our findings suggest that the market is relatively efficient in the REIT sector, and it is difficult for investors to devise trading strategies that improve the ex-ante performance of REIT portfolios, based on standard risk factors.
Keywords: Abnormal returns; Out-of-Sample; Portfolio management; Predictability; REITs; Real estate; dept.fin; peer-reviewed